Bricolage in Organizations - Pina e Cunha, Miguel (2005)
Theories of management and organization have traditionally overlooked the concept of bricolage. Focused on the rationality of resource allocation, scholars have missed the relevance of the skill of “inventing” resources from available materials. Changes in the nature of competition are, however, stressing the importance of speed and change as competitive factors in shifting environments. In these environments it may be impossible to search and wait for the presumably adequate resources. Bricolage, therefore, may be a relevant practice in these environments. This article discusses the concept of organizational bricolage by asking such questions as: What is bricolage? Why is bricolage a relevant practice? Why is bricolage so often ignored? How can it be facilitated?